Synthesis and Characterization of Co(II) Complexes with Some New Quinazolone Oximes - Rai, B.K.; Thakur, R.K.; Kumari, Minoo (Asian Journal of Chemistry, 2010)
A series of complexes having the formula Co(HL)2, Co(HL)2X2 and Co(HL)2Y2, where HL = 3-phenyl-quinazolone-4(3H) one-2-carboxaldehydoxime, X = CI-, Br-, r-, NO3- and CIO4- and Y = NH3 or pyridine have been synthesized by allowing ethanolic solutions of cobalt(II) salts to react with solution of the ligand in tetrahydrofuran in the molar ratio 1 : 2 and characterised by elemental analysis, molar conductivity, infrared spectra, electronic spectra and magnetic moment data. On the basis of experimental data the complexes of the type [Co(HL)2] are found to be square planar whereas complexes of the type [Co(HL)2X2] and [Co(HL)2Y2] are found to be octahedral. The complexes are found to be non-electrolytic in nature on the basis of low value of molar conductivities ..